The influence of different implant surfaces on osseointegration in diabetes: a systematic review of the literature - Fontanari, Lucas Amaral; Oliveira, Guilherme José Pimentel L; Basso, Túlio Luiz Durigan; Marcantonio Júnior, Elcio [UNESP]; Orrico, Silvana Regina Perez [UNESP]; Sampaio, José Eduardo Cezar [UNESP] (My University, 2014)
AIM: The aim of this study was to evaluate, through a systematic review of the literature, the effects of different implant surface modifications on osseointegration in diabetic subjects. METHODS: A search was performed of the PubMed database, using a combination of the following keywords: “Implant surface” OR “Dental implants” AND “Diabetes” OR “Hyperglycemia”. Papers published in English between January 1960 and November 2013 were selected. All experimental models were considered in this search, but case reports and in vitro studies were excluded from this review. RESULTS: The initial search identified 182 articles. After reading the titles and abstracts, 39 articles were selected for full reading. Finally, 4 papers were selected after evaluation of all the papers, and these papers are discussed in this review. Due to the methodological heterogeneity of the selected studies, it was not possible to perform a meta-analysis of the data. CONCLUSION: It can be concluded that although the benefits of surface modifications present in individuals with diabetes have biological plausibility, there is little evidence of the benefits of these modifications.